2010
DOI: 10.1371/journal.pone.0013836
|View full text |Cite
|
Sign up to set email alerts
|

BK Channels Mediate Cholinergic Inhibition of High Frequency Cochlear Hair Cells

Abstract: BackgroundOuter hair cells are the specialized sensory cells that empower the mammalian hearing organ, the cochlea, with its remarkable sensitivity and frequency selectivity. Sound-evoked receptor potentials in outer hair cells are shaped by both voltage-gated K+ channels that control the membrane potential and also ligand-gated K+ channels involved in the cholinergic efferent modulation of the membrane potential. The objectives of this study were to investigate the tonotopic contribution of BK channels to vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 59 publications
3
68
1
Order By: Relevance
“…Because efferent synaptic inhibition acts as a parallel shunt, the inhibitory conductance must increase with "resting" membrane conductance to remain effective. Thus, larger synaptic contacts in the high-frequency basal region might be expected, as has been reported previously (46). Moreover, the fact that RT-PCR and in situ hybridization measurement of α9 expression shows both longitudinal and radial gradients, with the greatest expression over OHCs in basal regions (48), might indicate a higher density of nAChRs in the high-frequency region of the cochlea.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Because efferent synaptic inhibition acts as a parallel shunt, the inhibitory conductance must increase with "resting" membrane conductance to remain effective. Thus, larger synaptic contacts in the high-frequency basal region might be expected, as has been reported previously (46). Moreover, the fact that RT-PCR and in situ hybridization measurement of α9 expression shows both longitudinal and radial gradients, with the greatest expression over OHCs in basal regions (48), might indicate a higher density of nAChRs in the high-frequency region of the cochlea.…”
Section: Discussionsupporting
confidence: 64%
“…However, the increasingly calcium-permeable nAChR of rat cochlear hair cells might also indicate that stronger efferent inhibition is required for mammalian cochlear hair cells. It has been observed (44)(45)(46) and recently elaborated (47) that OHCs exhibit increasing membrane ionic conductance moving from apical, low-frequency positions to higher-frequency basal locations in the mammalian cochlea. This increased membrane conductance along with decreased capacitance (membrane area) confers shorter membrane time constants to high-frequency basal OHCs.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, we expect that relative contamination of the I K we measure by I K,n will be small. Interestingly, Wersinger et al (49) found that linoperdine at 100 -200 M was able to substantially block outward K ϩ currents in apical OHCs and suggested that KCNQ4 channels underlie the major component of the outward I K . It must be emphasized, however, that this drug will block both Kv2.…”
Section: C302mentioning
confidence: 99%
“…In contrast to this, the relative Ca 2+ to monovalent cation permeability ratio for the chicken recombinant 910 nAChR is much lower, a ratio of 2, which is similar to other nAChRs that do not contain the 910 subunits (50). The authors conclude that the evolutionary processes that were responsible for the increased Ca 2+ permeability of mammalian 910 nAChRs were specific to the mammalian lineage and happened concomitant with other adaptations that conferred high frequency hearing to mammals [27,[48][49][50] .…”
Section: Functions Of α9α10 Nicotinic Acetylcholine Receptorsmentioning
confidence: 81%
“…Both in vitro an in vivo models of inactivation of α9 nAChR-induced signaling using antagonists or RNA interference of keratinocyte as well as experiments in knockout mice delayed wound healing, and reduced colony scattering and In high frequency regions of the cochlea, in addition to the SK2 channels shown, BK channels (large conductance Ca 2+ and voltage-activated channels), are also expressed [48,49] . The ACh-induced conductance results in efferent modulation of the cell's excitability.…”
Section: Functions Of α9α10 Nicotinic Acetylcholine Receptorsmentioning
confidence: 99%